2008
DOI: 10.1044/1092-4388(2008/07-0070)
|View full text |Cite
|
Sign up to set email alerts
|

An Experimental Clinical Trial of a Cognitive-Behavior Therapy Package for Chronic Stuttering

Abstract: The CBT treatment was associated with significant and sustained improvements in psychological functioning but did not improve fluency.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
156
0
5

Year Published

2012
2012
2016
2016

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 220 publications
(168 citation statements)
references
References 43 publications
7
156
0
5
Order By: Relevance
“…These findings confirm that social anxiety is the primary concern for children who stutter in this sample. That is, when compared to matched controls, a significantly higher rate of social anxiety disorder was found for children who stutter (based on diagnostic assessment), and this was corroborated by significantly higher social anxiety scores (based on parent and child report symptom measures).Research with adults who stutter has also shown that social anxiety is the primary disorder reported when conducting diagnostic assessments (Blumgart et al, 2010; Iverach, Jones et al, ANXIETY DISORDERS AMONG STUTTERING CHILDREN 31 2009;Menzies et al, 2008;Stein et al, 1996). Hence, findings from the present study emphasize the potential for social anxiety to be the primary concern for children who stutter, with other forms of anxiety (e.g., separation anxiety, generalized anxiety) being of secondary concern for a smaller subset of children.…”
mentioning
confidence: 80%
“…These findings confirm that social anxiety is the primary concern for children who stutter in this sample. That is, when compared to matched controls, a significantly higher rate of social anxiety disorder was found for children who stutter (based on diagnostic assessment), and this was corroborated by significantly higher social anxiety scores (based on parent and child report symptom measures).Research with adults who stutter has also shown that social anxiety is the primary disorder reported when conducting diagnostic assessments (Blumgart et al, 2010; Iverach, Jones et al, ANXIETY DISORDERS AMONG STUTTERING CHILDREN 31 2009;Menzies et al, 2008;Stein et al, 1996). Hence, findings from the present study emphasize the potential for social anxiety to be the primary concern for children who stutter, with other forms of anxiety (e.g., separation anxiety, generalized anxiety) being of secondary concern for a smaller subset of children.…”
mentioning
confidence: 80%
“…20,22 Speech-focused cognitive behavioral therapy has been shown to decrease social anxiety and psychological distress in adults who stutter. 23 Our finding that patients may be hesitant to discuss or even disclose their stuttering to physicians raises concerns about missed opportunities to diagnose and treat mental health problems associated with stuttering. Fortunately, we found that a trusting relationship between patient and physician can allow patients the latitude to discuss their stuttering and how it might affect their lives.…”
Section: Discussionmentioning
confidence: 98%
“…We grouped participants into three focus groups based on age category (18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(30)(31)(32)(33)(34)(35)(36)(37)(38)(39)(40)(41)(42)(43)(44)(45)(46)(47)(48)(49), 50+ years) with the goal of enhancing participants' comfort discussing health-related information. All focus groups were conducted by H.R.P., a physician who stutters, during the NSA conference, and lasted 45-60 min.…”
Section: Data Collectionmentioning
confidence: 99%
“…The association between developmental stuttering and diminished psychological wellbeing has been extensively documented (Craig, Blumgart and Tran, 2009;Craig and Hancock, 1995;Craig and Tran, 2014;Iverach, O'Brian, Jones, Block, Lincoln, Harrison, Hewat, Menzies, Packman and Onslow, 2009;Iverach and Rapee, 2014;McAllister, Collier and Shepstone, 2013;McAllister, Kelman and Millard, 2015;Menzies, O'Brian, Onslow, Packman, St Clare, and Block, 2008). In particular, social anxiety disorder, an excessive and persistent fear or expectancy of negative evaluation in situations involving social interaction (American Psychiatric Association, 1994;Beck, Emery, & Greenberg, 1985) has been shown in several studies to be much more prevalent in adults who stutter than in the general population (Blumgart, Tran and Craig, 2010;Iverach and Rapee, 2014;Iverach et al, 2009;Menzies et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…In particular, social anxiety disorder, an excessive and persistent fear or expectancy of negative evaluation in situations involving social interaction (American Psychiatric Association, 1994;Beck, Emery, & Greenberg, 1985) has been shown in several studies to be much more prevalent in adults who stutter than in the general population (Blumgart, Tran and Craig, 2010;Iverach and Rapee, 2014;Iverach et al, 2009;Menzies et al, 2008).…”
Section: Introductionmentioning
confidence: 99%